Evidence-based development of a post-surgical lumbar discectomy leaflet intervention: a Delphi consensus study. Issue 3 (11th March 2015) - Goodwin, P C; Wright, C C; Allan, C; Crowther, L; Darley, C; Heap, A; Paul, E; White, L; Rushton, A
Abstract : Objective: To produce free, expert-informed postoperative information for lumbar discectomy patients, satisfying UK National Health Service Information Standards. Design: A mixed methods approach utilising the Delphi technique and focus groups. Setting: Five spinal centres across the UK. Participants: Panel members included 23 physiotherapists, 11 patients and 17 spinal surgeons. Intervention: Three rounds of questionnaires including open and closed questions and attendance at a clinician/patient focus group. Results: Response rates of 85%, 26% and 35% were achieved for the Delphi rounds. Ten clinicians and six patients participated in the focus groups. Consensus for leaflet sections was achieved in round 1 and content in round 3. The focus groups informed further revisions. Conclusions: A consensually agreed, Information Standard compliant, patient lumbar discectomy leaflet was produced containing: (1) normal spine anatomy; (2) anatomy disc herniation and surgery; (3) back protection strategies and (4) frequently asked questions. Illustrations of exercises enable tailoring to the individual patient.